El control interno y su incidencia en el departamento de recaudaciones del gobierno autónomo descentralizado municipal del cantón. Quevedo año 2013. - Manobanda Villamar, Ivonne Alexandra (2015)
Today public institutions have evolved progressively implementing technology and introducing administrative and accounting tools that facilitate decision-making, assessment of activities and achievement of objectives. The investigation of internal control systems, provide assurance that the various administrative tools provided help to be prepared for any contingency that may arise. The management carried out by the department of revenue of the Autonomous Government Decentralized Municipal Canton Quevedo should be evaluated on an ongoing basis, which is why this process was supported in scientific and technical methods such as observation, surveys and interviews, as well as other means of finding data. The Autonomous Decentralized Municipal Government Quevedo Canton maintains a level of confidence regarding controls in the state of 49.6%, 50.4% causing Risk Level Control. It was found that in the collections department does not have a manual functions and rules of procedure, which has not allowed defining the goals and objectives that the institution should be addressed. Management indicators showed that the efficiency and effectiveness of operations to develop the Autonomous Decentralized Municipal Government Quevedo Canton employee in 2013, presents a percentage: 28.6% efficiency, effectiveness 33.33% .Once the assessment made to internal control it was determined that the acceptable audit risk is 1.92%, which corresponds to a low percentage reliability of accounting systems in the department ... It was also found that employees are not trained, no monitoring plans are made and no have established criteria for evaluating staff performance